DUBBING MOVIE TO INCREASE SPEAKING SKILL OF TENTH GRADE STUDENT™S OF SMA NEGERI 15 MEDAN - Br Ginting, Febrianty Adma Gloria; Sumarsih, Sumarsih; Oktora, Maya (TRANSFORM: Journal of English Language Teaching and Learning, 2020)
The study was aimed to recognize how a teaching method could increase students™ competence in speaking. The objective of the study is to describe how the dubbing movie increases the students speaking skill of the tenth Grade Students  of SMA N 15 Medan. The research design is a qualitative research. The data collecting methods were interview, observation, and documentation. The data gained was analyzed by using Miles and Huberman model of the data analysis. The research found that the students of the Grade X in SMA N 15 Medan enjoyed the process of preparing the video dubbing from the announcement, script preparing, and the practice. Some students who noticed difficult in speaking English were found increase in speaking competence especially in languages expression and found a fun way to practice English speaking. For short, the video dubbing teaching method increased the students of SMA N 15 Medan English speaking competence.